Safe sex and the Rambo/Bimbo divide: A look at the gender Imperative of AIDS: Wilton, T (1997) Engendering AIDS: Deconstructing sex, text and epidemic. London: Sage Publications. - Leclerc-Madlala, Suzanne (PINS-Psychology in Society, 2026)
As a social scientist engaged in researching AIDS and evaluating AIDS prevention programs in southern Africa, I have always been dismayed by the lack of preparatory "ground-work" for understanding the context in which this epidemic was occurring. AIDS prevention/education programs just seemed to spring up everywhere in the past decade, with program directors actually believing that it was only a matter of not having proper knowledge about AIDS. Give them the necessary knowledge and behavioural change would follow. Sadly, it didn't happen. Ten years later we are just coming to grips with the complexity of it all.